Photobiomodulation Does Not Increase Mitochondrial Respiration in Skeletal Muscle or Skin Tissue in Humans - Thorben Aussieker; Heather L. Petrick; Lisa M.E. Kuin; Jeremias Kaiser; Cas J. Fuchs; Esther Kornips; Kostas Tsintzas; Scott Cooper; Sandra Lammers; Stephan Praet; Tim Snijders; Luc J.C. van Loon (Medicine & Science in Sports & Exercise, 2026)
Purpose: Low-level laser therapy, also referred to as photobiomodulation (PBM), is rapidly gaining popularity as a non-invasive treatment for various conditions and as a means to enhance health and performance. PBM has been proposed to directly increase mitochondrial activity in skin and skeletal muscle and activate various molecular signalling pathways. However, evidence for the proposed properties of PBM in vivo in humans is lacking. Methods: In a within-participant study design, 12 healthy men and women (6/6 m/f; age: 25±6 y; BMI: 23.3±2.2kg/m 2 ) received PBM on a randomized leg, while the other leg received sham-treatment (no light emitted, CON). Three cycles of PBM or sham-treatment were performed for 5 min 16 sec each (5.6 kJ light energy/cycle for PBM). Skin temperature was measured before and after treatment. After treatment, skin and muscle samples were collected from both legs. Mitochondrial respiration was measured in permeabilized muscle fibers and minced skin tissue using an Oroboros Oxygraph-O 2 k. Muscle metabolic gene expression was assessed using custom made microfluidic cards. Results: Skin temperature increased only in the PBM treated leg (+8.0±1.4 °C; P